Metodologia para condução do teste de germinação e produção de mudas em diferentes substratos de Quillaja brasiliensis - Cantos, Alexandra Alves (2013)
This study aimed to determine the conditions for seed germination test and evaluate the best substrate for the production of seedlings of species of Quillaja brasiliensis (A.St. - Hil & Tul) Mart. The seeds of Q. brasiliensis were sown four replications of 25 seeds in paper substrates and sand as recommended by the RAS. Sowing was between paper, on paper, between sand and on sand subjected to a constant temperature of 20 º C. First count of germination (PCG) was analyzed, and germination speed index (GSI), mean germination time (MGT) and determination of moisture content of the batch worked (U ).Two arrays were used for seed collection, located on the edge of the riparian zone of the Arroio Lavras do Sul, RS. For the assessment of germination in different substrates for the production of seedlings via seed , the following materials and compositions : T1 : Vermiculite , T2 : Coconut Fiber , T3 : Commercial Substrate , T4 : 50% carbonized rice husk ( CAC ) + 50 % vermiculite , T5 : 50 % CCS and 50 % coconut fiber. The tests were performed in trays of polystyrene, four replicates of 36 seeds were used. Each seed was covered with a layer of 1 cm substrate for testing for germination and seedling performance. The experiment was conducted for 120 days, during this period, the trays remained in the laboratory, receiving natural light (indirect) and subject to fluctuations in temperature and RH (%) of the environment . The following variables were analyzed to compare the performance of substrates: shoot height, ratio of height of shoot and root, length of taproot, number of lateral roots , number of leaves. In the assessment of seedling competitions we sought to determine the influence of the number of seeds per cell in 72 cells polystyrene tray with vermiculite + carbonized rice husk ( CAC) in 50:50 ( % ) in the emergence of seedlings. Seed of the same batch of those used in the performance tests as a function of substrate were used. Seeds were distributed in four replicates of 11 cells, distributed by treatments: T1 : one seed per cell, T2 : two seeds per cell, T3 : three seeds per cell and T4 : four seeds per cell. The experiment was conducted for 60 days and assessed according to the seedling emergence or not and depending on the number of cells in which seedlings had emerged. The moisture content was determined by the use of two replicates 1g of intact seeds. It was concluded that for the test laboratory germination the seeds are sown in the paper substrate and methodologies on paper and paper roll. The first count of germination should be performed on the sixth day after sowing and the test ended on the 14th day after sowing. The indicated photoperiod is 16 hours of light at a constant temperature of 20 ° C. To assess the production of seedlings it is concluded that expanded vermiculite is a suitable substrate. In the production of seedlings is recommended to use the trays three seeds per cell and subsequently perform thinning with removal of the less vigorous seedlings.